Implementing Work Safety Based on the Positive Psychological Approach of Qur'an - Sunarno, Sunarno; Fakih, Zainun Kamaludin; Sarnoto, Ahmad Zain (Interdisciplinary Social Studies, 2023)
Background: Work safety is urgently needed in the workplace. Occupational safety includes physical and psychological. The concept of occupational safety focuses not only on the safety of the body but also on the state of mind and ruhani by using concepts that are in the Qur 'an with a psychological approach. So with the concept of safety work, accidents in the work world can be prevented as much as possible. Aim: The purpose of this study is to know the concept of occupational safety based on positive psychology of the Qur’an. Method: As for the methods used in this study are qualitative methods and library research, thematic and sampling. The study used a psychological approach to figure out the psychological concepts in the Qur 'an to bring up theories of occupational safety the Qur 'an's perspective. Findings: This study has shown that occupational safety focuses not only on the use of physical security but on every work related to such things as society policy, rules, mental preparation, increased human resource capacity (human resources), into specific ways by carrying out certain traditions to achieve work safety. In the Qur 'an, there is the word "amil" that leads to the prevention of occupational accidents. "Amil" can mean a measure of good, fair, and virtuous.